Determination of competencies for the teachers of the subject of competences of the Arabic language in the semester system and the course system in the city of Jeddah - Al-Ghamdi, Amal Ali (Journal of Educational and Psychological Sciences, 2018)
The study aimed to determine the competencies required for the teachers of the competences of the Arabic language in the semester system and the course system in Jeddah. The researcher used the descriptive descriptive method. The sample of the study consisted of a random sample of 250 teachers from the schools of the semester system, Jeddah, a questionnaire was constructed consisting of (50) paragraphs divided into three areas. Using the Statistical Processes of the SPSS program, the results of the study showed the following: First: The degree of competence required for the teachers of the Arabic Language competencies in the semester system and the course system in Jeddah came to a great degree of appreciation. The average score was 4.10. The competencies of the Arabic language in the semester system and the course system in Jeddah on the fields of study as follows: The field of planning with a great degree of degree, with a mean average of (4.09), the field of implementation with a large degree of identification, an average of 4.11, Hit (4.10). In light of the results of the study, the researcher presented a number of recommendations and proposals aimed at activating the competences of the Arabic language, the most important of which is: Emphasizing the institutions of preparing the female teachers to guide the competencies in the preparation of the secondary stage teachers. Supervisors of the Arabic language in the list of competencies while supervising the education in secondary schools. Taking into consideration that competencies are taken into consideration when evaluating female students in field education during secondary school. To review the programs for the preparation of parameters, especially the specialization of Arabic language teachers to match with the global variables and local data. The need to prepare training courses for teachers working to gain them and adjust their performance in relation to the competencies addressed by the current study.